2007
DOI: 10.1021/om700425d
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening of Cyclohexene via Metathesis by Ruthenium Carbene Complexes. A Computational Study

Abstract: Cyclohexene (CH) metathesis reaction mediated by the second-generation ruthenium alkylidene catalyst (IMesH2)(PCy3)CI2RuCHPh (1a), ruthenium ester carbene complexes (IMesH2)(PCy3)CI2RuCHCOOMe (1b), and (PCy3)2CI2RuCHCOOMe (1c), where IMesH2 is a 1,3-dimesityl-4,5-dihydroimidazol-2-ylidene group, has been modeled at the PBE0/LACV3P**++//PBE0/LACVP* level of theory. The calculations revealed that the necessary condition for the catalyst to be active in CH ring-opening is the existence of a high-energy π-compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…mechanism 23 -25 and in the prediction of the reactivity of many challenging olefins. 26,27 Various theoretical aspects of reactions involving cyclic olefins have been studied. 28 -30 However, no attention has been paid to the peculiarities of the ring opening metathesis of the highly strained monocyclic cyclopropene moiety.…”
Section: Introductionmentioning
confidence: 99%
“…mechanism 23 -25 and in the prediction of the reactivity of many challenging olefins. 26,27 Various theoretical aspects of reactions involving cyclic olefins have been studied. 28 -30 However, no attention has been paid to the peculiarities of the ring opening metathesis of the highly strained monocyclic cyclopropene moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Because of their stability and the ease of handling, both Ru-based catalysts and the mechanism of olefin metathesis by ruthenium carbene complexes were the subject of intense experimental [19][20][21][22][23][24][25][26][27][28] and detailed computational studies. [18,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] From the results of comprehensive calculations on the mechanism of olefin metathesis [19,29] it was concluded that for 2 nd -generation Grubbs catalysts, the formation of the 14-electron active species via the dissociation of phosphane is rate limiting, whereas for 1 st -generation Grubbs catalysts the barrier for metallocyclobutane (MCB) formation is the rate limiting step. The origin of the high activity of 2 nd -generation Grubbs catalysts in alkene (CH 2 --CH 2 ) metathesis was also studied quantum chemically by Straub.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases we assume that the active 14‐electron ruthenium alkylidene intermediate 2 is formed at the beginning of the process after the dissociation of both 3‐bromopyridine ligands. The dissociative mechanism is commonly accepted for olefin metathesis and other reactions catalyzed by the Grubbs‐type ruthenium alkylidene complexes . Moreover, the phosphine‐free catalysts are known to be more active than the systems bearing phosphine ligands because of the more labile character of the 3‐bromopyridine ligands .…”
Section: Resultsmentioning
confidence: 99%